Regulation of autophagy by perilysosomal calcium: a new player in β-cell lipotoxicity - Ha Thu Nguyen; Andreas Wiederkehr; Claes B. Wollheim; Kyu‐Sang Park (2024)
Autophagy is an essential quality control mechanism for maintaining organellar functions in eukaryotic cells. Defective autophagy in pancreatic beta cells has been shown to be involved in the progression of diabetes through impaired insulin secretion under glucolipotoxic stress. The underlying mechanism reveals the pathologic role of the hyperactivation of mechanistic target of rapamycin (mTOR), which inhibits lysosomal biogenesis and autophagic processes. Moreover, accumulating evidence suggests that oxidative stress induces Ca